Palladium on Plastic Substrates for Plasmonic Devices - Paola Zuppella; Elisabetta Pasqualotto; Sara Zuccon; Francesca Gerlin; Alain Jody Corso; Matteo Scaramuzza; Alessandro De Toni; Alessandro Paccagnella; Maria Guglielmina Pelizzo (Sensors, 2015)
Innovative chips based on palladium thin films deposited on plastic substrates have been tested in the Kretschmann surface plasmon resonance (SPR) configuration. The new chips combine the advantages of a plastic support that is interesting and commercially appealing and the physical properties of palladium, showing inverted surface plasmon resonance (ISPR). The detection of DNA chains has been selected as the target of the experiment, since it can be applied to several medical early diagnostic tools, such as different biomarkers of cancers or cystic fibrosis. The results are encouraging for the use of palladium in SPR-based sensors of interest for both the advancement of biodevices and the development of hydrogen sensors.